Acoustic Analysis of Fish Tanks for Marine Bioacoustics Research - Jesús Carbajo; Pedro Poveda; Naeem Ullah; Jaime Ramis (Journal of Marine Science and Engineering, 2025)
Underwater sounds play a key role in biodiversity as many marine animals use these to know their environment and to communicate among themselves. Unfortunately, anthropogenic noise makes this communication more difficult due to masking effects and may also produce harmful effects that compromise their preservation and survival. Many researchers have studied the influence of underwater noise on marine species in laboratory conditions using fish tanks. Consequently, studying the acoustic response of these fish tanks constitutes an essential task to better understand the results obtained in those experiments. In this work, a theoretical model and acoustic measurements were used to assess the uncertainty of a fish tank setup. The proposed methodology aims to improve the effectiveness of those studies involving fish tanks by an in-depth analysis of the sound field spatial distribution. Preliminary results show that this distribution depends on the frequency of the generated sound, the water level, and the measurement depth thus confirming the importance of analyzing the range of applicability of these setups.